Protection of Geographical Indications (GIs) in India - Shafiulla, B. (Prabandhan: Indian Journal of Management, 2013)
The issue of Geographical Indications (GIs) has been debated in India and globally at various forums like the World Trade Organization (WTO). World Intellectual Property Organization (WIPO) provides for the protection of GIs at an international level. 'Geographical Indication' refers to an indication of goods that have originated from a definite geographical territory, used for identifying an agricultural, natural or manufactured good. Examples of GIs in India are Basmati Rice, Kanchipuram Silk Sari, Tellicherry Pepper, Nilgiris Tea, Darjeeling Tea etc. In India, Protection and Registration of GIs relating to goods comes under The Geographic Indications of Goods (Registration and Protection) Act, 1999 and the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) deals with GIs' protection at international levels. GIs have rapidly gained importance, and the WTO has initiated actions to legalize the registration of goods as GIs in the context of an increasing integrated international regime. Major objectives of this study are: i) To understand GIs in India through overview of GIs protection, registration and the challenges faced by GIs protected-agricultural, natural and manufactured- goods in the Indian context. ii) Effort has been made to identify the difference between GIs and Trademarks through this research. iii) An overview of few GIs registration of goods in India has been conducted to know how GIs have been protected and further scope for GI registration for more goods has been explored. iv) In the present study, efforts have also been made to find out the benefits and challenges of GI certification for various goods in the Indian context. The major challenges faced by goods applying for GI status are: Origin of the goods for identifying geographic territory; Registration of GIs; Monitoring and controlling specified processes, procedure and quality of GI protected goods; Protection of GIs from infringement; and enforcement of intellectual property rights.